A Real‐Time Self‐Adaptive Thermal Metasurface - Guo, Jun; Xu, Guoqiang; Tian, Di; Qu, Zhiguo; Qiu, Cheng‐Wei (Advanced materials (Weinheim), 2022)
Emerging metamaterials have served as an efficient strategy for the realization of unconventional heat control and management using structural thermal properties, and many functional thermal metadevices have been investigated. However, thermal functions are usually fixed or limited in the switching range. Thus far, real‐time thermal regulation is elusive for thermal metamaterials because of deterministic artificial metastructures and uncontrollable phase transitions, coupled with the absence of dynamic adaptability. Here, a self‐adaptive metasurface platform to implement programmable thermal functions via the automatic evolution of thermoelectric heat sources and real‐time control of the driven voltage is reported. The proof‐of‐concept smart platform experimentally demonstrates arbitrary switching between elaborate thermal patterns consolidated into an active thermoelectric element matrix. Further, thermal pixels and feedback control systems are integrated into printed circuit boards, resulting in self‐adaptability to any thermal requirements. This study sets up a new paradigm for arbitrary transitions between exquisite thermal patterns and is expected to pave the way for real‐time thermal management in a programming formation. A self‐adaptive metasurface platform for real‐time thermal regulation is presented. The proof‐of‐concept platform experimentally demonstrates arbitrary switching between elaborate thermal patterns consolidated into an active thermoelectric element matrix. The thermal pixel matrix and feedback control system are integrated into a universal system. This work may pave the way for real‐time thermal management in programming formations.